THE CORRELATION BETWEEN STUDENTSâ SELF-EFFICACY AND THEIR PERFORMANCE IN SPEAKING SKILL - Sari, Ni Putu Yanti Cahya (IKIP Mataram, 2016)
This study is generally attempted to find the correlation between studentsâ self-efficacy and their performance in speaking skill at the second grade of SMPN 18 Mataram in academic year 2017/2018 .The method of the research applied is correlation research (explanatory design). The population of this research consist of three clasess of SMPN 18 Mataram Â which number 59 population and theÂ sample of the study is 52 students. The sample technique used in this research is simple random sampling technique by using slovin formula. Based on the result of the study, there was correlation between self-efficacy and their performance in speaking skill in which r-test (0,80) > r-table (0,268), its means the value of r-test was higher than r-table. From the research data it was found out that there was significant correlation between studentsâ self-efficacy and their performance in speaking skill. This was proved by the t-test score (7,957) was higher than t-table (1,675) the degree of freedom (df) was used 50. It can be concluded that self-efficacy and their performance in speaking skill has significant correlation at the second grade students of SMPN 18 Mataram. Finally, the researcher suggests that should be more creative to make students self-efficacy increased in using media or strategy that students do not feel bored in the class. Â